Current Evidence and Future Projections: a Comparative Analysis of the Impacts of Climate Change on Critical Climate-Sensitive Areas of Papua New Guinea - Patrick S. Michael (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2019)
Climate change is a global concern arising from spatial or temporal changes in precipitation, temperature and greenhouse gases. The impacts of this on critical climate-sensitive areas are largely on land, marine resources, forestry and agriculture, and their biodiversity and ecosystems. In Papua New Guinea (PNG), the mainstay (85%) of the rural people is on land and agriculture, compared to resources obtained from the marine areas and forest. Productivity on land depends on climatic factors and a compromised climate affects land, which in turn affects forestry, agriculture and the marine environment (resources and ecosystems). Because of this, a lot of resources have been invested in climate change to understand the impacts; however, much is yet to be achieved, especially in the developing nations. In PNG, understanding the types of changes in climate that will be experienced is important to be resilient, to mitigate and to adapt. In this review, the potential impact of global climate change on climate of PNG and the impact of the new (future) climate on land, marine and forest resources and their biodiversity and ecosystems are analyzed. Moreover, the impacts on crop agriculture are discussed. Analysis of available data shows that the temporal and spatial changes in precipitation and temperature projections of the future climate are within current optimum crop production ranges, at least up to 2090. Since most staple and plantation crops in PNG are C3 plants, an increase in CO2 levels will have a fertilizing effect on productivity. The plastic effects on certain crops may benefit some farmers as temperature, precipitation and CO2 levels change.